Hubungan Pengetahuan Ibu Hamil tentang Manfaat Senam Hamil terhadap Proses Persalinan di Puskesmas Ampelgading - Eva Lestiatul; Rosyidah Alfitri (Pusat riset dan Inovasi Nasional, 2025)
Pregnancy is divided into three stages: the first trimester, second trimester, and third trimester. During pregnancy, the body undergoes various changes that can cause discomfort. Common discomforts experienced by pregnant women include varicose veins, back pain, muscle and joint aches, and lower back pain. These discomforts can be alleviated through pregnancy exercise (prenatal yoga or maternity gymnastics). The purpose of this study was to examine the relationship between pregnant women’s knowledge about the benefits of pregnancy exercise and the childbirth process at Ampelgading Public Health Center. The research design used was descriptive quantitative. The population consisted of 35 pregnant women in May 2025, with a total sampling technique. Data were collected using a questionnaire and analyzed using univariate analysis. The results showed that 36 respondents (50.0%) had moderate knowledge, 25 respondents (34.7%) had poor knowledge, and 11 respondents (15.3%) had good knowledge about pregnancy exercise. Overall, most pregnant women had a moderate level of knowledge. Based on the Spearman Rank statistical test with a 95% confidence level, the P-value was 0.000 (< 0.05), indicating a statistically significant relationship. The conclusion of this study is that there is a relationship between pregnant women's knowledge of the benefits of pregnancy exercise and the childbirth process at Ampelgading Public Health Center.